Business Subsidies in Canada Comprehensive Estimates for the Government of Canada and the Four Largest Provinces - John Lester (The School of Public Policy Publications, 2018)
Business subsidies in Canada: the “winner” is Alberta; the loser is the taxpayer The federal government and the four largest provinces in Canada spend about $29 billion a year on business subsidies, delivered through program spending, the tax system, government business enterprises and direct investments by government. These subsidies represent almost half of the corporate income tax revenue collected by the five jurisdictions.